Prenatal Diagnosis of Atrioventricular Communication in the Fetus as a Method of Predicting the Outcome of Surgical Treatment after the Child’s Birth - Shapoval, L. A; Kurkevych, A.; Rudenko, N. M; Yemets, I. M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Atrioventricular communication (AVC) is one of the most common heart diseases diagnosed prenatally (1–5). According to various studies, among all of congeninal heart diseases diagnosed in fetus, AVC accounts for 17 %. Abortion and fetal death significantly affect this indicator, as among all the congenital cardiac abnormalities AVC accounts for only 4–5 % in live births (4, 6). There are many anatomical variants of the defect. And frequent combination of the defect with additional cardiac, extracardiac and chromosomal abnormalities significantly impacts both the prognosis for the fetus with AVC and the outcome of surgical treatment of the defect after birth. The aim. To analyze the range of cases of prenatally diagnosed AVC in the fetus and evaluate further outcome of surgical treatment, depending on the anatomical features of the anomaly and associated additional cardiac, extracardiac and chromosomal abnormalities. Materials and methods. From January 2014 to December 2017, 4343 pregnant women were screened at the Prenatal Diagnostics Department of the UCCC of the Ministry of Health of Ukraine. During fetal echocardiography, 1247 fetuses were diagnosed with congenital heart defects, 215 (17.2 %) of them had AVC. We analyzed the data of fetal echocardiography in fetuses with AVC and compared them with postnatal data. Results. AVC was diagnosed in 215 fetuses and confirmed in 120 newborns. The average age of the mother was 29.9 ± 5.4 years (range 17–46). The average gestation period was 24.7 ± 4.9 weeks (range 17–39). At the time of primary consultation, fetal cariotype was known in 45 (20.9 %) cases, chromosomal abnormalities were detected in 30 (14 %) of fetuses. AVC without any other intracardiac malformations was revealed in 111 (51.6 %) of the fetuses. Extracardiac anomalies were detected in 104 (48.3%) of the fetuses. In 87 (40.5 %) cases, there was an abortion. One hundred twenty (55.8 %) pregnancies ended with term birth, and in 8 (3.7 %) cases fetal death was reported. Of 8 cases of fetal death, in 4 cases AVC was an isolated pathology, in the other 4 it was combined with additional intracardiac defects. Of the 120 born alive, 63 (28.8 %) infants died during the first months of life without receiving cardiac surgery. Only 57 (26.5 %) patients had surgical treatment. Of 215 fetuses with prenatally diagnosed AVC, chromosomal pathology was detected in 66 (30.7 %) newborns, 63 (29.3 %) of whom had Down syndrome. The spectrum of anatomical variants of AVC diagnosed prenatally significantly differed from the data obtained after the birth of a child, especially with regard to the higher incidence of complex intracardiac defects found in fetus. In the postnatal period, AVC was more likely to be seen as an isolated variant of the pathology. In our observation, chromosomal abnormalities associated with AVC were detected in 66 (30.7 %) newborns, 63 (29.3 %) of them had Down syndrome (p = 0.001). Other heart defects and extracardiac pathology were diagnosed in 48.3 % and 37.2 % of cases, respectively. The survival of fetuses with isolated and combined AVC was 53.1 % and 58.7 %. Of the 120 born alive, 28.8 % of infants died during the first months of life. Surgical treatment was performed in only 26.5 % of patients (p = 0.001). The overall survival rate during the three-year follow-up period was 27.9 % for patients with isolated AVC and 15.4 % for patients with combined AVC. Conclusion. Our data confirm a large variety of the spectrum of anatomical variants of AVC found in fetus. AVC frequently combines with additional intracardiac defects, and less frequently is associated with chromosomal or extracardiac anomalies, however, this suggests less favorable prognosis for further surgical treatment, mainly in the presence of additional intracardiac pathology.